TINJAUAN KRIMINOLOGI TENTANG SEBAB-SEBAB ORANG MELAKUKAN TINDAK PIDANA PENCABULAN (Studi Putusan PN Demak No.115/Pid.Sus/Dmk 10 Agustus 2016). - Ragil Wahyuningsih, Safik Faozi (Fakultas Hukum Universitas Stikubank, 2019)
The occurrence of crime is caused by several factors, namely criminal biology, criminal psychology, and criminal sociology. Even though there are many factors related to an offender committing an act of sexual abuse based on that basis, I took a research entitled: